General equation of a circle is in this form: (x-h)^2+(y-k)^2=r^2
The question gave you just few information that you need to complete it by completing the square (I.e collect the x's in one barract and y's in other barract and numbers on the other side of the equation.
If you still don't know what to do here you can find the answer:
Just complete the square by diving the no infront the variable (With degree of 1) by 2 then square it
eg. 2x , 2/2=1 , then square 1 which is 1
by doing that in the question we get:
(x-1/3)^2+(y-3/2)^2= -2+1/9+9/4 = 13/36
A is correct.